2015
DOI: 10.1039/c5cc01239b
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia detection by using flexible Lewis acidic sites in luminescent porous frameworks constructed from a bipyridinium derivative

Abstract: A flexible bipyridinium ligand with Lewis acidic sites has been introduced into two isomorphous metal-organic frameworks to yield luminescent porous materials with subtriangular pore windows, which exhibit sensitive fluorescent response for ammonia molecules and can be proved at the molecular level by Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…The gas coordination effect can not only quench the luminescence of the lanthanide metal ions but also perturb the excited state energy of the organic fluorophore . For example, Dincaˇ et al reported two MOFs [Zn 2 (tcpe)(H 2 O) 2 ]·4DEF and [Mg(H 2 dhbdc)(DMF) 2 ] (H 4 tcpe = tetrakis(4‐carboxyphenyl)ethylene, DEF = N , N ‐diethylformamide, H 4 dhbdc = 2,5‐dihydroxybenzene‐1,4‐dicarboxylic acid) showing shifts of emission wavelengths upon interaction with ammonia at 100 °C ( Figure ) .…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…The gas coordination effect can not only quench the luminescence of the lanthanide metal ions but also perturb the excited state energy of the organic fluorophore . For example, Dincaˇ et al reported two MOFs [Zn 2 (tcpe)(H 2 O) 2 ]·4DEF and [Mg(H 2 dhbdc)(DMF) 2 ] (H 4 tcpe = tetrakis(4‐carboxyphenyl)ethylene, DEF = N , N ‐diethylformamide, H 4 dhbdc = 2,5‐dihydroxybenzene‐1,4‐dicarboxylic acid) showing shifts of emission wavelengths upon interaction with ammonia at 100 °C ( Figure ) .…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…The characteristic peaks at 1638 cm À 1 for 1, 1635 cm À 1 for 2, 1639 cm À 1 for 3 are attributed to viologen ligands. [25]…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the number of CUMSs was determined through surface acid site titration employing NH 3 as probe molecule. NH 3 is an ideal probe molecule since it is small (kinetic diameter of 2.6 Å) and allows titration of weak acid sites [90]. Total surface acidity was assessed from the net weight gain recorded after an isothermal adsorption step of NH 3 at 100 • C followed by removal of physisorbed molecules with a He stream.…”
Section: Density Of Coordinatively Unsaturated Metal Sites (Cumss)mentioning
confidence: 99%